Manajemen Perilaku Organisasi Mahasiswa Sekolah Tinggi Agama Islam Negeri Jember: Managing Student Organizational Behavior at the State Islamic Institute of Jember - Ali Saifullah (Fenomena, 2003)
Student demonstrations at STAIN Jember increasingly exhibit anarchic and excessive tendencies, deviating from intellectual, sensitive, and moral frameworks. Guided by Spearman and Burt’s behavioral theories and Freud’s psychoanalytic perspective, this study addresses the need to develop skilled management strategies for student organizations, examines whether protests reflect intellectual parameters or emotional impulses, and explores integrating skilled management with organizational behavior. Using a qualitative case study design, data were collected through comprehensive interviews, participant observation, and documentation, employing snowball sampling and grounded theory analysis. Findings reveal that student organizations lack skilled management, with static structures and work programs, while student criticism is often driven by specific interests rather than substantive intellectualism. Furthermore, institutional systems at STAIN Jember—such as nontransparent governance and authoritarian policies—provoke reactive demonstrations. The study concludes that restructuring skilled management, reforming institutional systems toward transparency and adaptability, and modeling intellectual, sensitive, and moral behavior by leaders are essential to restoring credibility and fostering responsible academic activism. Demonstrasi mahasiswa STAIN Jember cenderung menunjukkan tindakan anarkis dan berlebihan, menyimpang dari kerangka intelektualitas, sensibilitas, dan moralitas. Berpijak pada teori perilaku Spearman dan Burt serta psikoanalisis Freud, penelitian ini bertujuan merumuskan manajemen terampil bagi organisasi mahasiswa, mengkaji apakah demonstrasi merupakan parameter intelektualitas atau emosi, serta mengintegrasikan manajemen terampil dengan perilaku organisasi. Dengan pendekatan kualitatif studi kasus, data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan dokumentasi, menggunakan teknik snowball sampling serta analisis grounded theory. Temuan menunjukkan organisasi mahasiswa belum memiliki manajemen terampil; struktur dan program kerja bersifat statis, sementara kritik mahasiswa lebih didorong kepentingan tertentu而非 substansi intelektual. Sistem kelembagaan STAIN Jember yang kurang transparan dan otoriter turut memicu aksi reaktif. Penelitian menyimpulkan bahwa penataan manajemen terampil, reformasi sistem menuju keterbukaan dan adaptabilitas, serta keteladanan perilaku intelektual, sensitif, dan bermoral dari pimpinan mutlak diperlukan guna memulihkan kredibilitas dan menghasilkan aktivisme akademik yang bertanggung jawab.